2021
DOI: 10.1016/s2468-2667(21)00066-9
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to residential neighbourhood characteristics and risk of 79 common health conditions: a prospective cohort study

Abstract: Background Observational studies have identified a link between unfavourable neighbourhood characteristics and increased risk of morbidity, but it is unclear whether changes in neighbourhoods affect future disease risk. We used a data-driven approach to assess the impact of neighbourhood modification on 79 health outcomes. MethodsIn this prospective cohort study, we used pooled, individual-level data from two Finnish cohort studies: the Health and Social Support study and the Finnish Public Sector study. Neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…2) [25,61,62]. In line with these studies, and suggesting causal relationship, natural experiments and studies of residential relocation show that moving to low deprivation neighbourhoods reduces HbA 1c and risk of type 2 diabetes [42,63,64]. Despite growing evidence for the relationship between social capital and health [65], the few studies investigating social capital and type 2 diabetes incidence present mixed findings [61,[65][66][67][68].…”
Section: Social Environmentmentioning
confidence: 82%
See 1 more Smart Citation
“…2) [25,61,62]. In line with these studies, and suggesting causal relationship, natural experiments and studies of residential relocation show that moving to low deprivation neighbourhoods reduces HbA 1c and risk of type 2 diabetes [42,63,64]. Despite growing evidence for the relationship between social capital and health [65], the few studies investigating social capital and type 2 diabetes incidence present mixed findings [61,[65][66][67][68].…”
Section: Social Environmentmentioning
confidence: 82%
“…A systematic review showed that interventions to increase physical activity by changes in the built environment generally improved levels of physical activity [41], but effects on type 2 diabetes have not been evaluated. Furthermore, a large Finnish cohort study of over 100,000 individuals showed that changes in residential greenness were associated with a 12% reduced risk of type 2 diabetes [42]. Finally, a meta-analysis showed an established association that urban dwellers, particularly in low-and middle-income countries, have a 40% increased risk of type 2 diabetes [26], but the underlying drivers of this association are not entirely clear.…”
Section: Stronger Evidencementioning
confidence: 99%
“…Of the 178 375 adults in the eligible population from the two Finnish cohorts, 117 583 (65•9%) participated in the baseline survey, 116 503 (65•3%) had data on height and weight, and 114 657 (64•3%) were successfully linked to national health registers and were included in the sample for primary analysis (figure 1). In the primary analysis population, the mean age at BMI assessment (baseline) was 42•6 years (SD 11•0), 86 632 (75•6%) were women and 28 025 (24 [18][19][20]. By contrast, obesity was associated with 28 of the 78 diseases studied (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We excluded hospitalisations due to obesity and focused on a predefined list of 78 common ICD-10 disease chapters and diagnostic groups constructed for outcome-wide studies by investigators who were masked to exposure data (including BMI). 20 …”
Section: Methodsmentioning
confidence: 99%
“…The neighborhood disadvantage score is based on the proportion of adults with low education, the unemployment rate, and the average annual income of households in each 250 m × 250 m grid area. 21,22 We replaced missing data (i.e., areas with fewer than 10 residents in the neighborhood) with the mean neighborhood disadvantage score of the eight adjacent map squares. For each of the three variables, we derived a standardized z score based on the total Finnish population (mean = 0, SD = 1).…”
Section: Characteristics Of Local Environmentsmentioning
confidence: 99%